Automated Design Exploration of the TALOS Wave Energy Converter Using the TOP-WEC Framework (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Despite significant investment and numerous prototype deployments, many wave energy converter (WEC) developers have struggled to achieve sufficient power production to attract long-term investment, leading to the failure of several companies. A key challenge has been the lack of rigorous early-stage design exploration and optimization, resulting in suboptimal device performance and limited commercial viability. To help address this problem, we present an automated design exploration of TALOS, a promising WEC concept developed by Lancaster University. Using the TOP-WEC framework (the Time-Domain Optimization Platform for WECs), which integrates custom meshing scripts, Capytaine, and HydroChrono, we systematically evaluate many different geometric and power take-off (PTO) configurations. Since TOP-WEC is built on generalized numerical modeling tools, it can be applied to a broad range of WEC concepts - making it a versatile solution for automated design exploration. By leveraging automated simulations and optimization routines, we assess multiple design variants against a baseline TALOS WEC to quantify performance improvements. The results demonstrate that targeted optimization can significantly enhance energy capture efficiency while maintaining practical design constraints. This work underscores the importance of comprehensive numerical modeling and the utility of Python APIs for automating design exploration during the early development stages of WECs - providing a powerful approach for advancing wave energy technologies towards more viable commercial deployment.